Implementasi Pemenuhan Hak Ketenagakerjaan Pekerja Perempuan di Perusahaan Perkebunan Kelapa Sawit Kabupaten Muaro Jambi yang Terafiliasi Sertifikasi ISPO, RSPO dan Non ISPO/RSPO - Wihabsari, Tri Astuti; Suandi, Suandi; Napitupulu, Dompak MT (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to describe the implementation of fulfilling the employment rights of female workers at 3 (three) palm oil plantation companies in Muaro Jambi Regency. This research uses the Mills & Huberman (1984) method. The research results show that in the palm oil plantation business hierarchy, women always occupy the affected levels, are limited in accessing work and career development, occupy temporary worker positions, are paid low wages and receive relatively little reproductive protection. The traditional view of stereotypes of suitability for work is the reason that occupational segregation based on gender has been maintained for generations, placing female workers in a weak position and in unfair working conditions. The number of genders doing a job is still the strongest basis for someone to classify jobs into men's and women's jobs. For the academic world and the business community in general, it is hoped that the results of this research will provide insight regarding the classification of gender-based job stereotypes, especially in Indonesia. Meanwhile, for industry, the results of this research can be a basis for creating gender-responsive labor regulations.